The influences of working memory representations on long-range regression in text reading: an eye-tracking study - Tanaka, Teppei; Sugimoto, Masashi; Tanida, Yuki; Saito, Satoru (Frontiers in Human Neuroscience, 2014)
The present study investigated the relationship between verbal and visuospatial working memory capacity and long-range regression (i.e., word relocation) processes in reading. We analyzed eye movements during a “whodunit task,” in which readers were asked to answer a content question while original text was being presented. The eye movements were more efficient in relocating a target word when the target was at recency positions within the text than when it was at primacy positions. Furthermore, both verbal and visuospatial working memory capacity partly predicted the efficiency of the initial long-range regression. The results indicate that working memory representations have a strong influence at the first stage of long-range regression by driving the first saccade movement toward the correct target position, suggesting that there is a dynamic interaction between internal working memory representations and external actions during text reading.